Contribution to the study of glucose metabolism in the cerebral cortex - Villavicencio Núñez, Marino (1962)
The main metabolic pathways following glucose into mammalian cells are shown in Fie. 1. From the quantitative point of view, the most important route is also called Embden Meyerhof glycolytic pathway. Under anaerobic conditions, the final product of glycolysis is lactic acid, while in the presence of oxygen, pyruvic acid enters the citric acid cycle to be oxidized to CO2 and water. However, some tumors and normal tissues, among which are the brain, are still significant amounts of lactic acid under aerobic conditions. Glycolysis and respiration are major mechanisms in the energy-producing mammalian cells.